2018
DOI: 10.1002/celc.201800441
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Fe2O3 Nanoparticles Anchored on Carbon Nanotubes as High‐Performance Anode for Lithium‐Ion Batteries

Abstract: Fe2O3 nanoparticles (<10 nm) anchored on carbon nanotubes (denoted as Fe2O3‐NPs@CNT) are synthesized by a facile electrophoretic deposition strategy. In the composite, CNTs are utilized to construct a conductive matrix for uniformly dispersing Fe2O3‐NPs, building up a hierarchically porous architecture. The Fe2O3‐NPs anchored on CNTs can function as active sites for electrochemical reactions and facilitate fast electrochemical reaction kinetics, endowing the composite with improved electrochemical reversibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…And the theoretical specific capacity of MgFe 2 O 4 calculated according this mechanism is about 804 mAh g −1 , corresponding to per mol MgFe 2 O 4 with a full conversion of Fe 3+ to Fe 0 . The initial discharge and charge capacities are 993 mAh g −1 and 683 mAh g −1 with an initial columbic efficiency of 68.7 %, which is similar to the results of other literatures ,. The widely accepted reasons are that on one hand, MgFe 2 O 4 nanoparticles with porous structure and high surface area consume more Li + to form the SEI film; on the other hand, the irreversible Li + insertion reaction (equation 1) also leads to the high irreversible capacity ,,,,.…”
Section: Resultssupporting
confidence: 84%
“…And the theoretical specific capacity of MgFe 2 O 4 calculated according this mechanism is about 804 mAh g −1 , corresponding to per mol MgFe 2 O 4 with a full conversion of Fe 3+ to Fe 0 . The initial discharge and charge capacities are 993 mAh g −1 and 683 mAh g −1 with an initial columbic efficiency of 68.7 %, which is similar to the results of other literatures ,. The widely accepted reasons are that on one hand, MgFe 2 O 4 nanoparticles with porous structure and high surface area consume more Li + to form the SEI film; on the other hand, the irreversible Li + insertion reaction (equation 1) also leads to the high irreversible capacity ,,,,.…”
Section: Resultssupporting
confidence: 84%
“…Extensive research has shown that ZnS nanostructures on combining with conductive carbon coating can improve electrical conductivity as well as surface areas, and hence proves to be a very promising strategy. Meanwhile, the nanostructured materials could offer a short diffusion path and quick reaction time ,. Various morphologies of materials including nanowires, nanosheets, nanoporous and nanotubes have been explored in the previous study .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the HRTEM image (Figure 7d) reveals that there are plentiful ultrafine amorphous nanoparticles being detected (noted by red circle) except for the crystalline Sn. On the grounds of the preceding reports [59,60], these ultrafine amorphous nanoparticles may be SnO 2 and Fe 2 O 3 -which accounts for the absence of diffraction rings of SnO 2 and Fe 2 O 3 in SAED pattern. Coupling the electron spectroscopy with the cyclic behavior, the characteristics of the surface and morphological integrity can become manifest in the production of steady and thin SEI layers, bringing forth the improved cyclic performance.…”
Section: Resultsmentioning
confidence: 79%
“…Nevertheless, the HRTEM image ( Figure 7d) reveals that there are plentiful ultrafine amorphous nanoparticles being detected (noted by red circle) except for the crystalline Sn. On the grounds of the preceding reports [59,60], these ultrafine To further disclose the structural elasticity/robustness, the micro-morphology of B-SFO@C subjected to 500 cycles at 1 A g −1 was further examined by SEM and TEM. As shown in Figure 7a, the cycled B-SFO@C electrode can still preserve a micron-sized construction well, without any cracks on its surface even if the surface is somewhat distinguished from that of the fresh B-SFO@C electrode.…”
Section: Resultsmentioning
confidence: 97%